New findings for diatomite (Diatomaceous earth) between the villages of manastir and Bešište (Mariovo) (Geologica Macedonica, 2016)
Diatomaceous earth as porous, fine granular siliceous sedimentary rock, due to their specific physical-chemical properties, often attracted attention to the study of professional and scientific aspect. For diatomaceous earth from the Manastir–Bešište deposit in geological literature very little has been written, especially its mineralogical and chemical composition. In the paper will be present the latest research and results obtained on samples taken from the surface of the ground from the Manastir–Bešište deposit. The test is made in the laboratories of the Faculty of Natural and Technical Sciences with X-ray diffraction and skanning electron microscope. From the X-ray powder diagram are seen most widespread mineral phases quartz, illite, muscovite, pyroxene, and amorphous phase.